The Wellbeing Analogy - Crespo, Ricardo (Cultura Económica, 2023)
The diversity of meanings or applications of “wellbeing” fuel a discussion about its context-dependence or not. This article will first introduce this discussion. Next, it will present the classical logical notion of analogy considering it as a possible answer to the discussion. After that, Section 3 will apply analogy to wellbeing and will suggest its possible “primary meaning”. Finally, a short conclusion will follow.